Inovasi Pelayanan (ELSIMIL) Pada Pelayanan Program Keluarga Berencana di Kecamatan Kradenan Kabupaten Grobogan - Aris Toening Winarni; Nova Munif I’tiskom (Public Service and Governance Journal, 2023)
Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction. The President appointed the National Population and Family Planning Agency (BKKBN) to be the Coordinator for Implementing the National Stunting Reduction. Stunting Prevention Strategy in the form of Ready for Marriage and Pregnancy (ELSIMIL) Electronic Applications used by prospective brides. This study aims to determine the suitability of Service Innovation (ELSIMIL) in Family Planning program services according to the characteristics of the community in Kradenan District, Grobogan Regency and to determine the factors of suitability and incompatibility between service innovations (ELSIMIL) and the characteristics of the people of Kradenan District, Grobogan Regency. . This research uses descriptive qualitative research method. Data collection techniques used interviews by interviewing the KB Service Unit Coordinator, District Admin, TPK (Family Assistance Team), Catin (Bride and Groom Candidates), observation and documentation studies. The results of this study are catin's habit of registering marriages in villages that are close to the time of marriage. The appropriate factor in the innovation of the ELSIMIL application service is that the target catin is still young, so making the application easy, there are many TPK in one village there are 12 TPK cadres. Factors that are not appropriate in the innovation of the ELSIMIL application service are many women who work outside the city, marriage registration in the village is also close to the time of marriage and many TPK are still confused about using the ELSIMIL application